DNA Damage Response and Autophagy: A Meaningful Partnership - Eliopoulos, Aristides G.; Havaki, Sophia; Gorgoulis, Vassilis G. (Frontiers in Genetics, 2016)
Autophagy and the DNA damage response (DDR) are biological processes essential for cellular and organismal homeostasis. Herein we summarize and discuss emerging evidence linking DDR to autophagy. We highlight published data suggesting that autophagy is activated by DNA damage and is required for several functional outcomes of DDR signaling, including repair of DNA lesions, senescence, cell death, and cytokine secretion. Uncovering the mechanisms by which autophagy and DDR are intertwined provides novel insight into the pathobiology of conditions associated with accumulation of DNA damage, including cancer and aging, and novel concepts for the development of improved therapeutic strategies against these pathologies.